A refined sinusoidal theory for laminated composite and sandwich plates. Issue 23 (1st December 2020) - Xiaohui, Ren; Zhen, Wu; Bin, Ji
Abstract: This paper proposes a new zig-zag function to develop the refined sinusoidal theory. A refined sinusoidal shear deformation theory can be obtained by including the proposed zig-zag function and meeting the traction-free boundary conditions on the top and the bottom surfaces. Governing equations and boundary conditions are obtained by using the principle of virtual displacement. Using Navier's method, analytical solutions are presented by solving the boundary value problem. By investigating the typical bending problems of laminated composite and sandwich plates, the effect of various parameters like aspect ratio, thickness ratio and material properties on the bending response of plate is studied in detail. Comparison of the present results with the three-dimensional elasticity solutions and the results calculated using other models published recently in the literature shows that the proposed theory can yield accurately the displacements and stresses of multilayered composite and sandwich plates. Moreover, the accuracy of the displacement and stresses are not impacted by the number of layers and the material properties.